The impact of related and unrelated mergers and acquisitions on company productivity: Panel data evidence from the UK - Girma, Michael (2006)
This dissertation reports on the impact of mergers and acquisitions on the general productivity and more specially labour productivity of acquiring firms in UK for the period 1981-1996. It reviews existing theoretical and empirical literature on the post merger performance in terms of productivity, accounting profits, stock return studies and labor productivity. The empirical section of this report uses an unbalanced panel of 887 plants taken from Data Stream for accounting information and London Share Price Data Base for information relating to mergers and acquisitions. The investigation is carried out in two ways: 1. First, the empirical models will assess if there is a permanent shift in productivity following a company's acquisition to related or unrelated business; 2. Secondly the sample is analysed according to size, industry type and finally, the effect is observed by time period. I found 6 principle results emerge from the analysis: 1. First, acquiring firms performance in terms of total factor productivity increases post merger compared to pre merger performance and firms that don't undertake any merger. 2. Second, performance increase of related mergers is more prominent than unrelated mergers. 3. Third, when the acquisition is taking place in smaller firms post merger productivity and labor productivity is higher than post merger performance of larger firms. 4. Fourth, when mergers occur in service industry post merger performance is lower than mergers occurring in manufacturing industry. 5. Performance of unrelated merger in large service industries is higher than post merger performance of related mergers in large service industries. 6. Finally, mergers that occurred with in 2 years after the market crashed in UK had the lowest post merger performance than the early 1980s and 1990s. Keywords: Mergers and Acquisitions, Related & Unrelated mergers, Total Factor Productivity (TFP), Labor productivity